Visual Quality Effect on Sustainability of Kampung Pelangi Semarang - Wuryaningsih, Teti Indrawati; Setioko, Bambang; Sari, Suzanna Ratih (Semarang State University, 2018)
Abstract : Kampung Pelangi Semarang has relatively dense buildings, spontaneously developed and lack of urban service facilities. The design of the area based on the aspects of physical quality, one of which is the visual quality. Visual signs are the main features that are physically visible. The core of this research is to identify the influence between visual quality and sustainability in Kampung Pelangi. The research method is quantitative, weighted using Likert scale and test by using linear regression analysis. Results from simultaneous research indicate that visual quality influences on sustainability in Kampung Pelangi. The magnitude of the influence of visual quality is only 44.7% of the sustainability, the rest of 52.3% is influenced by other factors, while partially regression analysis showed no influence from three variables. It means that there is still lack of diversity, dominance and clarity at the research locus, so it needs to be increased again with values of -3.9%, -2.6% and 5.8% respectively. It should be furtherly improved by adding coloring, marking and map themes, and adding various tourist attractions. For the other three variables, sequence, harmony, and uniqueness have an influence on sustainability in Kampung Pelangi, with the value of 19%, 17,1% and 17%, that the variables already exist in research locus but the value is very low so it must maintained and upgraded with the planning and implementation of proper programs to increase the level of sustainability there.